Synthesis, Characterization and Antioxidant Activity of Kobalt (II)-Hydrazone Complex - Yulyani Nur Azizah; Irma Mulyani; Deana Wahyuningrum; Damar Nurwahyu Bima (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2020)
The potency of the first-row transition metal complexes with Schiff's base ligand as an antioxidant has been widely studied by researchers. In this study, hydrazone-type Schiff base compounds, salicylaldehyde-2,4-dinitrophenylhydrazone (SDPH), resulted from the condensation of salicylaldehyde (1.5 mmol) and 2,4-dinitrophenylhydrazine (1.5 mmol) were synthesized and characterized with 1H-NMR. The synthesized SDPH was used as ligands in the formation of Co(II) metal complexes. The Co(II)-SDPH complexes were synthesized with reflux reaction at 60oC for 6 hours in molar ratio 1:3. Triethylamine is used to synthesis Co(II)-SDPH, which serves to deprotonate SDPH ligands. ESI-MS analysis showed that the complex is a neutral dimeric complex.The complex has the chemical formula [Co2(SDPH)2[(Et)3N]2(acn)2(OH)2 ([M+Na]+ = 1061 g/ mol), shown on the ESI-MS spectrum. Coordinate bonds between Co (II) metal ions with ligands are observed in the presence of shifting of the C=N wave number, as well as the loss of the vibrating peaks of the O-H groups to the infrared spectra of complexes. The IR spectrum of complexes was suggested that SDPH behave as a bidentate ligand through the azomethine nitrogen atom and phenolic oxygen atom. The ligand and its Co(II) complex have been screened for antioxidant activity against DPPH (2,2-diphenyl-1-picrylhydrazine). Based on the activity test results, the IC50 value of Co(II)-SDPH complex was lower than ligand. These results show that Co(II)-SDPH are potentials as antioxidants.